Strategi Guru IPS dalam Meningkatkan Kedisiplinan Belajar Siswa Kelas VIII di MTs Satu Atap Darul Istiqomah Bojonegoro - Rifda Amalia Putri (Universitas 45 Surabaya, 2024)
This study is backgrounded by facts on the field show that students of grade VIII at MTs One Roof Darul Istiqomah Bojonegoro still existed in no disciplinary behavior of waul even there were some students. This is demonstrated by researchers through observations and interviews regarding the discipline of deeds. The purpose of this study is to describe IPS Teacher Strategy In Improving Student Discipline Class VIII Student Learning Darul Istiqomah Bojonegoro MTs One Roof. This research is a kind of qualitative study with a case study approach. The subject in this study was a student of grade VIII MTs One Roof Darul Istiqomah Bojonegoro. Data Collection Techniques using interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion withdrawal. In addition, researchers use tringulais to perform the validity of data. The formula of problems in this study is : 1) How does the IPS teacher strategy in improving the discipline of class VIII student learning in MTs One Roof Darul Istiqomah Bojonegoro?, 2) Obstacles in improving the discipline of class VIII student learning in MTs One Roof Darul Istiqomah Bojonegoro? 3) How the solution and results of IPS teachers in improving the discipline of class VIII students in MTs One Roof Darul Istiqomah Bojonegoro. The results of this study show that: 1) The IPS Teacher Strategy In Improving Student Learning Discipline is the teacher giving advice and motivation to the students giving the discipline in writing which has been agreed by the MTs One Roof Darul Istiqomah Bojonegoro, the teacher will give points and punishment against students who commit violations. 2) The constraints in improving student discipline of class VIII students in MTs One Roof Darul Istiqomah Bojonegoro is a lack of awareness in students, lack of support from parents. 3) IPS solutions In Improving Student Discipline Class VIII in MTs One Roof Darul Istiqomah Bojonegoro is a teacher consistently performing policies according to the rules set in the sense that the teacher gives the punishment not as per the own accord but according to procedures and agreements set by MTs One Roof Darul Istiqomah Bojonegoro. As for the result, 96% can be said to be successful, it can not be said 100% successful because there are still some children who still commit violations.